Molecular subtype and growth hormone effects on dysmorphology in Prader–Willi syndrome. Issue 1 (29th November 2019) - Oldzej, Jeannine; Manazir, Javeria; Gold, June‐Anne; Mahmoud, Ranim; Osann, Kathryn; Flodman, Pamela; Cassidy, Suzanne B.; Kimonis, Virginia E.
Abstract: Prader–Willi syndrome (PWS) affects 1/15, 000–1/30, 000 live births and is characterized by lack of expression of paternally inherited genes on 15q11.2‐15q13 caused by paternal deletions, maternal uniparental disomy (UPD), or imprinting defects. Affected individuals have distinct physical features, and growth hormone (GH) deficiency occurs in some individuals with PWS. The aim of this study is to test the hypotheses that (a) individuals with deletions and UPD have different physical and dysmorphic features, (b) individuals treated with GH have different physical and dysmorphic features than those not treated, and (c) GH treatment effects are different for individuals with UPD in comparison to those with deletions. Study participants included 30 individuals with deletions or UPD, who did or did not have GH treatment. Participants' molecular abnormalities were determined by molecular and cytogenetic analysis. Clinical data were obtained by a single dysmorphologist. Individuals with deletions were found to be heavier ( p = .001), taller ( p = .031), with smaller head circumferences ( p = .042) and were more likely to have fair skin and hair than their family members ( p = .031, .049, respectively) compared to UPD patients. Females with deletions more commonly had hypoplastic labia minora ( p = .009) and clitoris (.030) in comparison to those with UPD. Individuals who received GH in both deletion and UPD groups were taller ( p = .004), had larger hands ( p = .011) and feet ( p = .006) and a trend for a larger head circumference ( p = .103). Interestingly, the GH‐treated group also had a lower rate of strabismus (esotropia [ p = .017] and exotropia [ p = .039]). This study showed statistically significant correlations between phenotype and molecular subtypes and also between phenotype and GH treatment.